The impact of carbohydrate, protein, and combined carbohydrate-protein supplementation on muscle damage and oxidative stress markers during prolonged cycling performance in the heat - Tarmast, D; Ghosh, A. (Asian Journal of Sports Medicine, 2024)
Background: The impact of oxidative stress (OS) on exercise performance and recovery depends on the mode, intensity, and duration of physical activity, which can lead to inflammation, fatigue, and muscle dysfunction. The effects of carbohydrate (CHO) and protein (PRO) supplementation, as well as their combination (CHO-PRO), on exercise performance remain controversial, particularly under normal and hot environmental conditions.